2020
DOI: 10.3390/ijerph17103401
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Changing Levels of Psychosocial Distress Scores across Pregnancy in Kenyan Women

Abstract: Background: Adverse childhood experiences (ACEs) have been associated with deleterious effects on mental health in pregnancy. Methods: The ACE International Questionnaire (ACE-IQ) was used to measure neglect, abuse, and household dysfunction. Longitudinal mixed effect modelling was used to test the effect of ACEs on pregnancy-related anxiety, depressive symptoms, and perceived stress at two time points (12–19 and 22–29 weeks) during pregnancy. Results: A total of 215 women who were predominantly married (81%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…Our findings are consistent with findings from both a low- and middle-income country (Kenya) [ 32 ] and a high-income country (USA) which showed an association between ACEs and depression/anxiety and perceived stress [ 33 , 34 ]. Women who endorsed that their own parents/guardians did not understand their childhood problems and worries also had slightly higher odds of comorbidity than those who endorsed that their parents/guardian understood their problems and worries.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with findings from both a low- and middle-income country (Kenya) [ 32 ] and a high-income country (USA) which showed an association between ACEs and depression/anxiety and perceived stress [ 33 , 34 ]. Women who endorsed that their own parents/guardians did not understand their childhood problems and worries also had slightly higher odds of comorbidity than those who endorsed that their parents/guardian understood their problems and worries.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of ACEs, both prospectively and retrospectively, is considerably higher than global and meta-analytic estimates [7]. However, ACEs evidence in low-income, high-violence settings with widespread adversity across the life course is slowly emerging [19,[87][88][89] and highlighting important similarities and differences in the field. Bt30 is one of few cohorts in an LMIC that has reached young adulthood-the period in which human capital disparities are likely to emerge [90].…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…Hence, a single adversity approach ignores the high probability that adversities co-occur and have an exponential impact. On the other hand, cumulative risk scores assume equal weighting of adversities while a number of studies have shown specific ACEs to be more deleterious than others [17][18][19]. Although there are currently no guidelines on the ACEs scoring in the available literature, some studies point to the 'four or more' cut-off functioning as a threshold level, with noticeable deviations in a range of outcomes at that mark [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to recent SLEs, adverse childhood experiences (ACEs), which are generally conceptualized as stressful early life events, have been closely linked to PND or PNA [17,18]. ACEs are defined as traumatic experiences that occur before 18 years including exposures to abuse, neglect, and household dysfunction [19], with 40-60% of pregnant women reporting at least one ACE [20][21][22][23]. A few studies have paid attention to the modifying effects of ACEs on SLEs regarding antenatal depression, and have suggested that ACEs could make pregnant women who have experienced SLEs more vulnerable to antenatal depression [24,25].…”
Section: Introductionmentioning
confidence: 99%